Improving Student Achievement with the Application of Smart Trainers Integrated QR Code - Wawan Purwanto; Hendra Dani Saputra; Dwi Sudarno Putra; Zainal Abadi Abadi; Ahmad Abadi Arif; Irma Wirantina Kustanrika (AEEJ : Journal of Automotive Engineering and Vocational Education, 2025)
The present research aims to demonstrate the enhancement of students' learning outcomes through the utilization of a smart trainer in conjunction with a QR code. This intelligent trainer is designed to display the voltage output values of each sensor on the motorcycle. Additionally, each sensor is designated a QR code, enabling students to comprehend the function of each sensor's performance and verify the theoretical principles linked with the corresponding QR code during practice. The educational method is implemented offline, comprising four sessions in phase F of the Merdeka curriculum. The cohort comprised 20 participants, consisting of 5 educators and 15 learners. The assessment results indicate that student learning outcomes enhanced following the provision of materials.